Prospects for the Development of Retail Payment Systems in Banks (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
As a result of improving the efficiency of retail payment in banks, the possibility of increasing competitiveness, full satisfaction of customer needs and profitability increases. This study explored various strategies and technologies that can be used to optimize retail banking operations. In addition, in the dissertation, ways to increase the efficiency of retail payments and reduce operational costs of banks were studied. It should be noted that banks that invest in these areas can achieve significant improvements in service delivery, operational efficiency and overall financial performance. Overall, this study provides a deeper understanding of how banks can use modern technological advances to improve retail payment efficiency.